2016
DOI: 10.1016/j.ijrobp.2016.06.427
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Simulation of Microscopic Dose Enhancement of Glucose Conjugated Gold Nanoparticles for the I-125 Radioactive Seeds Brachytherapy

Abstract: To investigate the microscopic energy deposition effect of glucose conjugated gold nanoparticles (Glu-GNPs) within a tumor irradiated by I-125 radioactive seeds on the nanometer/cell scale, and to quantify the corresponding microscopic dose enhancement factor (mDEF) around Glu-GNPs based on the real intra-cellular localization and spatial distribution of Glu-GNPs. Materials/Methods: The spectra of secondary electrons from atoms of gold and molecules of water under I-125 seeds irradiation of colorectal CL-187 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…DEFs for low-energy sources were calculated to be higher than those for higher-energy sources. Monte Carlo has also been utilized by Yang et al to explore the microscopic dose enhancement of glucose-conjugated GNPs for I-125 (Yang et al 2016). They found that dose is enhanced by 10-100X in regions 5-30 µm from the GNP surface.…”
Section: Introductionmentioning
confidence: 99%
“…DEFs for low-energy sources were calculated to be higher than those for higher-energy sources. Monte Carlo has also been utilized by Yang et al to explore the microscopic dose enhancement of glucose-conjugated GNPs for I-125 (Yang et al 2016). They found that dose is enhanced by 10-100X in regions 5-30 µm from the GNP surface.…”
Section: Introductionmentioning
confidence: 99%